Neuromuscular rate of force development deficit in Parkinson disease. (June 2017) - Hammond, Kelley G.; Pfeiffer, Ronald F.; LeDoux, Mark S.; Schilling, Brian K.
Abstract: Background: Bradykinesia and reduced neuromuscular force exist in Parkinson disease. The interpolated twitch technique has been used to evaluate central versus peripheral manifestations of neuromuscular strength in healthy, aging, and athletic populations, as well as moderate to advanced Parkinson disease, but this method has not been used in mild Parkinson disease. This study aimed to evaluate quadriceps femoris rate of force development and quantify potential central and peripheral activation deficits in individuals with Parkinson disease. Methods: Nine persons with mild Parkinson Disease (Hoehn & Yahr ≤ 2, Unified Parkinson Disease Rating Scale total score = mean 19.1 (SD 5.0)) and eight age-matched controls were recruited in a cross-sectional investigation. Quadriceps femoris voluntary and stimulated maximal force and rate of force development were evaluated using the interpolated twitch technique. Findings: Thirteen participants satisfactorily completed the protocol. Individuals with early Parkinson disease (n = 7) had significantly slower voluntary rate of force development ( p  = 0.008; d = 1.97) and rate of force development ratio ( p  = 0.004; d = 2.18) than controls (n = 6). No significant differences were found between groups for all other variables. Interpretations: Persons with mild-to-moderate Parkinson disease display disparities in rate of force development, even without deficits in maximal force. The inability to produce force at a rate comparable to controls is likely a downstream effect of central dysfunction of the motor pathway in Parkinson disease. Highlights: Strength and rate of force development deficits have been reported in Parkinson disease. The interpolated twitch technique is used to calculate a central activation ratio. Voluntary rate of force development is reduced compared to controls. Central activation ratio may change with disease progression and serve as an indicator of decline.